Exploring Factors Influencing Housewives’ Involvement In I-Suri in Malaysia: A Conceptual Study - Haneffa Muchlis Gazali (Penerbit UMS, 2023)
This conceptual study explores the factors influencing housewives' intention to participate in i-Suri, focusing on the significance of attitudes, subjective norms, awareness, and financial literacy. The study utilizes a theoretical framework based on the extended Theory of Reasoned Action (TRA) to provide insights for policymakers and financial institutions in Malaysia, enabling them to design targeted interventions and educational programs to promote i-Suri participation among housewives. Through a qualitative approach, the study establishes a conceptual understanding of the variables and their interrelationships. The study recognises the importance of awareness and financial literacy as crucial factors influencing intention formation. It is important to note that empirical evidence is not provided in this research. Thus, further research is recommended to empirically validate the applicability of TRA, awareness, and financial literacy in predicting i-Suri participation. Future studies should consider conducting quantitative research, incorporating a diverse sample representing various regions and socio-economic backgrounds to enhance the generalizability of the findings. The study's outcomes have implications for policymakers and practitioners promoting i-Suri participation. The findings emphasize the need for targeted interventions such as awareness campaigns and financial literacy programs to enhance housewives' understanding and knowledge of i-Suri. Additionally, creating a supportive social environment that encourages participation is crucial. Service providers can also benefit from the study's insights by improving their communication strategies to convey the advantages and features of i-Suri to housewives effectively. The study offers valuable guidance to policymakers, financial institutions, and service providers while acknowledging the need for further empirical research to validate and expand upon the conceptual findings.